2013
DOI: 10.1007/s00213-013-3274-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of repeated treatment with the dopamine D2/D3 receptor partial agonist aripiprazole on striatal D2/D3 receptor availability in monkeys

Abstract: Rationale Chronic treatment with dopamine (DA) receptor agonists and antagonists can differentially affect measures of DA D2/D3 receptor number and function, but the effects of chronic treatment with a partial D2/D3 receptor agonist are not clear. Objective We used a within-subjects design in male cynomolgus monkeys to determine the effects of repeated (17-day) treatment with the D2/D3 receptor partial agonist aripiprazole (ARI; 0.03 mg/kg and 0.1 mg/kg i.m.) on food-reinforced behavior (n=5) and on D2/D3 re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 51 publications
(57 reference statements)
0
10
0
Order By: Relevance
“…With regard to partial agonists, a recent PET imaging study in cynomolgus monkeys found that chronic aripiprazole, a D2R partial agonist, produced different effects on D2R binding potential: it appeared to increase binding when the subject had, on average, low D2R availability and decreased binding potential in monkeys with higher average D2R availability. 160 Thus, depending on the long-term consequences of cocaine or METH abuse on receptor availability, the effects of receptor partial agonists may be different than antagonists. There are behavioral nuances as well.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to partial agonists, a recent PET imaging study in cynomolgus monkeys found that chronic aripiprazole, a D2R partial agonist, produced different effects on D2R binding potential: it appeared to increase binding when the subject had, on average, low D2R availability and decreased binding potential in monkeys with higher average D2R availability. 160 Thus, depending on the long-term consequences of cocaine or METH abuse on receptor availability, the effects of receptor partial agonists may be different than antagonists. There are behavioral nuances as well.…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, the animals were sedated with 10-15 mg/kg ketamine and transported to the MRI Center where anesthesia was maintained via inhaled 1.5-3% isoflurane (Czoty and Nader 2015; Czoty et al 2013; Czoty and Nader 2012). The animals were artificially ventilated to control physiological parameters across animals.…”
Section: Methodsmentioning
confidence: 99%
“…The dopamine partial agonist aripiprazole is thought to down-regulate dopamine D2 receptor activity. We believe that this action results in improved brain function (Czoty et al, 2013) and may aid the psychotherapeutic process. Most patients were initially admitted to inpatient level of care before transition to PHP.…”
Section: Discussionmentioning
confidence: 98%
“…Those thresholds were chosen to ensure low weight individuals and allow any prescription of aripiprazole time to affect brain neurotransmitters (Czoty, Gage, Garg, Garg, & Nader, 2013). Furthermore, charts was inspected for diagnoses of major depressive or anxiety disorders that were supported by description of quality and number of symptoms to warrant diagnosis based on the Diagnostic and Statistical Manual of Mental Disorders (DSM-5) (American Psychiatric Association., 2013).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation